Sympatric and independently evolving lineages in the Thoropa miliaris – T. taophora species complex (Anura: Cycloramphidae) - Sabbag, Ariadne F. [UNESP]; Thomé, Maria Tereza C. [UNESP]; Lyra, Mariana L. [UNESP]; Brasileiro, Cinthia A.; Moriarty Lemmon, Emily; Lemmon, Alan; Haddad, Célio F.B. [UNESP] (Elsevier, 2022)
Species delimitation can be challenging and affected by subjectivity. Sibling lineages that occur in sympatry constitute good candidates for species delimitation regardless of the adopted species concept. The Thoropa miliaris + T. taophora species complex exhibits high genetic diversity distributed in several lineages that occur sympatrically in the southeastern Atlantic Forest of Brazil. We used 414 loci obtained by anchored hybrid enrichment to characterize genetic variation in the Thoropa miliaris species group (T. saxatilis, T megatympanum, T. miliaris, and T. taophora), combining assignment analyses with traditional and coalescent phylogeny reconstruction. We also investigated evolutionary independence in co-occurring lineages by estimating gene flow, and validated lineages under the multispecies coalescent. We recovered most previously described lineages as unique populations in assignment analyses; exceptions include two lineages within T. miliaris that are further substructured, and the merging of all T. taophora lineages. We found very low probabilities of gene flow between sympatric lineages, suggesting independent evolution. Species tree inferences and species delimitation yielded resolved relationships and indicate that all lineages constitute putative species that diverged during the Pliocene and Pleistocene, later than previously estimated.
Keywords: Anchored phylogenomics; Atlantic forest; Co-ocurring species; Independent lineages; Molecular species delimitation; Rock Frogs